Upcycling junk art and craft module to nurture creativity of children / Siti Zuraida Maaruf, Wan Nur Nadia Hanin Wan Abdul Hamid and Muhammad Faiz Sabri - Maaruf, Siti Zuraida; Wan Abdul Hamid, Wan Nur Nadia Hanin; Sabri, Muhammad Faiz (Universiti Teknologi MARA, Perak, 2021)
Up-cycling is a sustainable alternative incorporating the prevalent 3Rs of Recycle, Reuse, and Reduce of used items in campaigns to save the environment. The ‘DIY Art and Craft Activity Module’ is used as a scaffolding tool to enhance environmental awareness and its impact among primary school children through Visual Arts Education. This research utilised the Design Development Research Method (DDR) comprising of three phases namely; Phase 1: Needs Analysis, Phase 2: Design and Development, and Phase 3: Implementation and Evaluation. The data was collected by interviewing Visual Art teachers on the usability of the module and document analysis on the collection of artworks produced by students. Findings of this study demonstrated positive feedback from the teachers and students on the usability of the Junk Art module as supplementary learning material in order to enhance recycling awareness among Primary School students through Visual Art Education.